Die EZB muss die Inflation glaubwürdiger bekämpfen; The ECB has to tackle inflation more credibly - Maximilian Horst; Daniel Stempel; Ulrike Neyer (Wirtschaftsdienst, 2022)
– Inflation rates in the euro area have reached historic highs due in large part to high energy prices. As the euro area is a net importer of energy, one refers to this inflation as imported inflation. There is a danger that these high inflation rates will become entrenched in inflation expectations. This would not only imply that high inflation rates will persist but it could also cause a dangerous upward price spiral. Consequently, the ECB should communicate more clearly and more credibly that it will counteract this danger and act accordingly as the costs of disinflation will remain higher the longer the ECB waits to act.
Keywords: E31; E52; E58; 330; Inflation; Geldpolitik; Eurozone; Inflation; Geldpolitik; Eurozone